A layered beam element for modeling de‐bonding of steel bars in concrete and its detection using static measurements. Issue 4 (29th January 2018) - Liu, K.; Law, S.S.; Zhu, X.Q.
Summary: In the formulation of finite elements, the variation of elemental internal forces and displacements are interpolated. The force interpolation functions are known to reproduce the variations of forces better than the interpolation functions on the displacements. Layered section beam model is not as complicated as the fiber model, and yet, it is much more accurate than ordinary beam model. The force‐based finite element is revisited in this paper with its application in the numerical studies of a damage detection strategy for a reinforced concrete beam under static load. Two kinds of damages are studied including the cracking or other local damage of the concrete and the bonding between the concrete and the steel bar. Both kinds of damages in an element can be detected separately or in combinations with the proposed strategy. The force‐based layered finite element is shown to be a practical, accurate, and efficient representation of the bonding damage of steel bars in concrete structures.